On discrete value distribution of certain compositions - Garbaliauskienė, Virginija; Karaliūnaitė, Julija; Macaitienė, Renata (Mathematical Modelling and Analysis, 2019)
In the paper, we obtain universality theorems and a lower estimate for the number of zeros for the composition F ζ (s, α; a, b) , where F is an operator in the space of analytic functions satisfying the Lipschitz type condition, and ζ (s, α; a, b) is a collection consisting of periodic and periodic Hurwitz zeta-functions.First Published Online: 21 Nov 2018